2019
DOI: 10.3390/en12203969
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Marker for the Detection of Insulating Paper Degradation in Transformer Insulating Oil

Abstract: This manuscript presents a comprehensive literature review with the aim to provide readers a reference document with up-to-date information on the field of methanol use as a chemical marker. It has been a little more than a decade since methanol was first introduced as a marker for assessing solid insulation condition in power transformers. It all started when methanol was identified in the laboratory during thermal ageing tests carried out with oil-immersed insulating papers and was subsequently also identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 66 publications
(193 reference statements)
1
6
0
Order By: Relevance
“…The simulation results of the catalytic mechanism are consistent with several significant experimental studies [44]- [46]. It has been reported that the main degradation mechanism of cellulose is acid hydrolysis, especially for the amorphous region [15], [44], [47], [48]. With the aging of cellulose insulation, a large amount of low-molecular-weight acids (e.g.…”
Section: Effect Of Different Reaction Conditions On the Formationsupporting
confidence: 86%
“…The simulation results of the catalytic mechanism are consistent with several significant experimental studies [44]- [46]. It has been reported that the main degradation mechanism of cellulose is acid hydrolysis, especially for the amorphous region [15], [44], [47], [48]. With the aging of cellulose insulation, a large amount of low-molecular-weight acids (e.g.…”
Section: Effect Of Different Reaction Conditions On the Formationsupporting
confidence: 86%
“…In order to study the correlation between methanol content in oil and insulation state of transformer paper, it is necessary to realize high-precision quantitative measurement of methanol in oil produced by aging of transformer insulating paper. The methanol concentration in the oil produced by the aging of transformer paper is the lowest at the ppb level, and the ordinary gas chromatograph cannot achieve that detection accuracy [71,72]. On the other hand, the composition of the aged insulating oil is very complex.…”
Section: Gas Chromatography and Mass Spectrometry (Gc-ms)mentioning
confidence: 99%
“…As a result, some DP estimation models based on 2-FAL have been proposed [15]. It must be noted that when TUK paper is used in the transformer, the presence of 2-FAL is low compared to standard Kraft paper transformers for an equivalent DP value [16]. According to [16], a new aging indicator is needed with the increasing use of TUK paper in modern transformers that produce a small amount of 2-FAL compared to standard Kraft.…”
Section: Literature Reviewmentioning
confidence: 99%